ROLAND BATHES' SEMIOTICS IN YUNI FILMS - Suparto, Diryo; Septiadini, Dea (Sean Institute, 2022)
Gender stereotypes are one of the social issues constructed from the existence of social control in society. Gender stereotypes are not only encountered in social life but are also often depicted in a film, one of which is Yuni's film. Yuni film is a film that raises several social issues related to issues in Indonesia. The purpose of this study was to find out the gender stereotypes depicted in Yuni's film. This research is a type of qualitative research with a descriptive type of research. Researchers classify scenes that describe gender stereotypes in Yuni's films into 3 gender theories, namely, nature theory, nurture theory, and equilibrium theory, then these data analyzed using Roland Barthes's Semiotic analysis model. The results of the study obtained that there were 23 scenes and 27 images depicting gender stereotypes in Yuni's film with 11 themes obtained through 3 gender theories, namely 9 themes in nurture theory, 1 theme in nature theory, and 1 theme in equilibrium theory. This shows that the gender stereotype in Yuni's film is not a standard rule but a result of social construction.